THE ROLE OF THE SCHOOL IN THE FACE OF OPPOSITIONAL DEFIANT DISORDER (ODD): CHALLENGES AND INCLUSIVE STRATEGIES (CIPEEX, 2025)
Oppositional Defiant Disorder (ODD) is a neurodevelopmental disorder characterized by persistent behaviors of opposition, hostility, and disobedience directed at authority figures, usually emerging in childhood and significantly affecting students’ academic performance, group interaction, and socialization. The presence of these behaviors challenges the educational environment and requires schools to implement pedagogical strategies that ensure not only access but also the permanence and integral development of diagnosed children. This qualitative and descriptive study aimed to investigate how schools have dealt with the challenges imposed by ODD, analyzing the inclusive practices employed and identifying alternatives that promote a more equitable education. The method used was based on a literature review, analysis of academic productions, official documents, and legislation related to school inclusion, addressing aspects of child development, teacher training, and pedagogical practices applied in contexts of diversity. The results indicated that facing ODD in the school environment required intentional planning, pedagogical sensitivity, and the adoption of differentiated methodologies capable of accommodating the behavioral particularities of students and promoting a collaborative and respectful learning environment. It became evident that the construction of effective strategies depended on the continuous involvement of teachers, the support of the school management team, and the articulation between school, family, and health professionals, configuring an interdisciplinary and integrated approach. It was concluded that strengthening pedagogical awareness of ODD expanded the possibilities of inclusion and overcoming the barriers faced by students, contributing to the formation of a school environment that values diversity and ensures the fundamental right to quality education.
Keywords: Disorders; Education; Inclusion; Learning